Analysis of monetary policy and financial stability: a new paradigm - Charles A. E. Goodhart; Carolina Osorio; Dimitrios P. Tsomocos (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper introduces agent heterogeneity, liquidity, and endogenous default to a DSGE framework. Our model allows for a comprehensive assessment of regulatory and monetary policy, as well as welfare analysis in the different sectors of the economy. Due to liquidity and endogenous default, the transmission mechanism of shocks is well defined, and their short to medium run effects on financial stability are properly captured.
Keywords: D50; E43; E44; E50; G01; G20; 330; general equilibrium; financial fragility; monetary policy; regulation